Studies on Harvesting, Processing and Utilization of Calamus tenuis Roxb. (Cane) Grown at Dehra Dun - Sharma, B. K.; Chaudhari, D. C. (Indian Forester, 1987)
The results of series of experiments conducted for proper scientific method of harvesting, collection, drying and processing of Calamus lenuis an all purpose cane have been reported in this paper. It Is observed that this indigenous cane matches well in general appearence, strength, etc., with the imported and reputed ’Singapore’ cane.